Hormesis of 2,4-D choline salt in productive aspects of cotton - Marques, Ricardo F. [UNESP]; Araújo, Prissila P. S.; Pinheiro, Guilherme H. R.; Souza, Rodrigo M.; Martins, Dagoberto [UNESP]; Marchi, Sidnei R. (Taylor & Francis, 2021)
The stimulating effect of a low dose of a substance considered to be toxic is known as hormesis. The aim of this work was to use dose-response curves to evaluate the hormesis effect provided by sub-doses of the herbicide 2,4-D choline salt on the productivity of cotton at different phenological stages. The experimental design was based on randomized blocks, with four repetitions and the treatments were distributed in a 9x3 factorial design, with nine fractions of the mean label dose of the herbicide 2,4-D choline salt formulation (0 (control); 0.4275; 0.855; 1.71; 3.42; 8.55; 17.1; 34.2 and 68.4 g a.e. ha−1) associated with three different phenological stage of cotton, namely: V4, B4 and C4. The plants were evaluated as to the main productive parameters of the cotton plant. When applied at the V4 stage, sub-doses of the herbicide 2,4-D choline salt negatively affect the cotton crop. Sub-doses between 0.82 and 2.23 g a.e. ha−1 of the herbicide 2,4-D choline salt applied at the B4 stage of cotton can increase all the productive variables of the crop. The productive aspects of cotton plants in the C4 stage were not influenced by the application of sub-doses of 2,4-D choline salt.
Keywords: 2,4-dichlorophenoxyacetic acid; Gossypium hirsutumL; hormesis effect; productivity; synthetic auxin